Human ehrlichiosis - Đokić Milomir; Ćurčić Petar; Nožić Darko; Lako Branislav; Begović Vesna; Rajić-Dimitrijević Radmila; Hristović Dejan (Vojnosanitetski Pregled)
Background. Human ehrlichiosis is a newly recognized disease. It is a tick-borne disease caused by several bacterial species of the genhus Erlichia. These are small gram-negative pleomorphic cocci, that are obligatory intracellular bacteria. Tick Ixodes is the principle vector in Europe, and Amblyomma americanum in the United States. Bacterial organisms replicate in a tick, and are transmited from infected cells in a vector to the blood cells of animals or humans. Human ehrlichiosis is a name for a group of diseases caused by different species of Ehrlichia. One of them is the disease named human monocytic ehrlichiosis, caused by Ehrlichia chaffeensis, and the other is a human granulocytic ehrlichiosis caused by Anaplasma phagocytophilia. Case report. We reported a 23-year-old patient admitted for the clinical treatment with the symptoms of high febrility (above 40 °C), headache, vomiting, general weakness and exhaustion, but without data on a tick bite. The patient was treated with trimetoprim-sulfamethoxazole for a week when Ehrlichia chaffeensis was confirmed by the immunofluoroscence test, and the therapy contimed with doxacyclin. Conclusion. Human ehrlichiosis is also present in our country, so this disease should be considered everyday, especially in infectology practice.